2022
DOI: 10.1124/dmd.122.000862
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Xenobiotic Receptors in Metabolic Diseases

Abstract: Metabolic diseases are a series of metabolic disorders that include obesity, diabetes, insulin resistance, hypertension, and hyperlipidemia. The increased prevalence of metabolic diseases has resulted in higher mortality and mobility rates over the past decades, and this has led to extensive research focusing on the underlying mechanisms. Xenobiotic receptors (XRs) are a series of xenobioticsensing nuclear receptors that regulate their downstream target genes expression, thus defending the body from xenobiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 186 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…As a key xenobiotic receptor, the functions of PXR in regulating xenobiotic metabolism have been extensively investigated by many groups and the role of PXR as a xenobiotic sensor has been established Kliewer et al, 2002;Zhou et al, 2009b). New evidence has suggested novel functions of PXR beyond xenobiotic metabolism, and several studies have also indicated that PXR may play an important role in obesity and metabolic disorders (Zhou, 2016;Zhang et al, 2023). However, the cell type-specific functions of PXR in obesity have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key xenobiotic receptor, the functions of PXR in regulating xenobiotic metabolism have been extensively investigated by many groups and the role of PXR as a xenobiotic sensor has been established Kliewer et al, 2002;Zhou et al, 2009b). New evidence has suggested novel functions of PXR beyond xenobiotic metabolism, and several studies have also indicated that PXR may play an important role in obesity and metabolic disorders (Zhou, 2016;Zhang et al, 2023). However, the cell type-specific functions of PXR in obesity have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from our laboratory and others revealed novel functions of PXR in cardiometabolic disease including obesity, diabetes and cardiovascular disease (CVD) beyond xenobiotic metabolism (Bhalla et al, 2004;Kodama et al, 2004;Kodama et al, 2007;de Haan et al, 2009;Zhou et al, 2009a;Cheng et al, 2012;He et al, 2013;Spruiell et al, 2014a;Spruiell et al, 2014b;Sui et al, 2015;Zhou, 2016;Helsley and Zhou, 2017;Gwag et al, 2019;Zhang et al, 2023). Several studies have also investigated the function of PXR in obesity and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…PXR and CAR are transcription factors and have since been defined as master regulators of xenobiotic responses through their transcriptional regulation of drug-metabolizing enzymes and transporters, including CYPs (Poudel et al, 2022). Activation of PXR and CAR is also associated with the development of numerous metabolic diseases (Zhang et al, 2022). At a molecular level, when a drug, which can induce CYP expression, is taken up into a metabolic cell, it can serve as a ligand to bind to either PXR or CAR in its ligand binding domain.…”
Section: Induction Of Cyp Expression By Drugs Through Activation Of X...mentioning
confidence: 99%